2(3n- 1)
2(2 + 3 n-1)
2 n + 2
2(3n+2)
Correct answer is A
T1=4;T2=10;T3=16
T2−T1=T3−T1=6
Tn=a+(n−1)d
= 4+(n−1)×6
= 4+6n−6
= 6n−2
= 2(3n - 1)
Find α and β such that x38 x y−67 x (\(\frac{y^{\frac{9}{...
The angle between the positive horizontal axis and a given line is 135°. Find the equation of th...
The nth term of a sequence is given 31 - n , find the sum of the first terms of the sequence....
In the diagram above angle LNM and angle YNZ are represented by g and h respectively. Find &ang...
Two fair coins are tossed at the same time. what is the probability of getting a head? ...
if P and Q are fixed points and X is a point which moves so that XP = XQ, the locus of X is ...
Find the value of x for which the function y = x3 - x has a minimum value. ...
If P and Q are two statements, under what condition would p|q be false? ...
In the figure, 0 is the centre of the circle ABC, < CED = 30o, < EDA = 40o. What is the size o...